Dual-Polarization Distributed Feedback Fiber Laser Sensor Based on Femtosecond Laser-Inscribed In-Fiber Stressors for Simultaneous Strain and Temperature Measurements - Guo, Kuikui; He, Jun; Xu, Gaixia; Wang, Yiping (IEEE access, 2020)
We propose and experimentally demonstrate a novel dual-polarization distributed feedback fiber laser (DFB-FL) sensor based on femtosecond laser-inscribed in-fiber stressors. The resonant cavity of the DFB-FL sensor consists of a phase-shifted fiber Bragg grating (PS-FBG) in the fiber core of a section of heavily erbium-doped fiber (EDF), together with two stressors in the fiber cladding around the PS-FBG. The PS-FBG was fabricated by means of a scanning UV laser beam and shielded phase mask technique. The two in-fiber stressors, i.e. a sawtooth stressor and a straight stressor, were directly inscribed at two orthogonal planes in the EDF cladding using a near-infrared femtosecond laser. The two stressors could precisely adjust the fiber birefringence in the laser cavity, and hence the DFB-FL sensor can operate in two polarization modes. Moreover, simultaneous measurement of axial strain and temperature was demonstrated by detecting the polarization beat frequency ν _{B} and lasing wavelength λ of the dual-polarization DFB-FL sensor. Experimental results exhibit strain sensitivities of 34.5 kHz/ μ ε , 1.25 pm/ μ ε and temperature sensitivities of 684.6 kHz/°C, 11.5 pm/°C, respectively. As such, the proposed dual-polarization DFB-FL sensor could be used for simultaneous strain and temperature measurements, and hence is promising for application in many areas, such as smart structures and intelligent robotics.